O teorema do homorfismo de grupos. - SOARES, Karla Miani de Sousa (Universidade Federal do Tocantins, 2023)
In this work we present an introduction of Groups Theory with emphasis on group homomorphism. Our main goal is to enunciate and demonstrate the Homomorphism Theorem. This theorem gives us a characterization of the quotient group of the do- main of a homomorphism by its nucleus and an explicit way of obtaining from a ho- momorphism a quotient group. For this, we do a whole study on group isomorphism.